Computed tomographic features of inflammatory myofibroblastic tumour of the stomach in adult patients: An analysis of five multicentre cases with literature review. Issue 6 (3rd August 2018) - Lee, Ji Eun; Choi, Seo‐Youn; Lee, Hae Kyung; Yi, Boem Ha; Lee, Min Hee; Lee, Sunyoung; Lee, So Jung; Lee, Jisun; Jeong, Woo Kyoung
Abstract: Introduction: The aim of this study was to describe the clinical and computed tomography (CT) features of gastric inflammatory myofibroblastic tumour (IMT) in adult patients and provide a review of the literature. Methods: Five adult patients with surgically resected and pathologically confirmed gastric IMT were included in the study from four tertiary referral centres. Clinical history was assessed for determination of patient demographics and symptoms at presentation. All patients underwent contrast‐enhanced abdominal CT, and two radiologists assessed the CT features by consensus. Also, abdominal CT findings from previous case reports of nine adult patients with gastric IMT were reviewed and summarised. Results: Of five gastric IMTs, four (80%) appeared as a well‐defined subepithelial mass and only one (20%) appeared as an irregular wall thickening. All of five gastric IMTs showed strong enhancement. When we analysed the CT features of nine cases from previously published literatures combined with our five cases, predominant imaging feature of gastric IMT was a well‐defined subepithelial mass with strong enhancement. Perigastric infiltration or direct invasion of the neighbouring organs was rarely seen. Conclusion: Gastric IMT in adult patients appeared either as a well‐defined subepithelial mass or irregular wall thickening, with mostly strong enhancement. Although rare, these imaging feature may be helpful for diagnosis of gastric IMT.